Advancements in mTOR Inhibitors for Non-Small-Cell Lung Cancer: Mechanisms, Efficacy, and Future Perspectives - Thaker, Aanal; Patel, Shrusti; Dey, Rajdeep; Shaw, Suman; Bhatt, Hardik; Patel, Bhumika; Chaube, Udit (Synlett, 2025)
This account comprehensively reviews the recent advancements in the development of mechanistic target of rapamycin (mTOR) inhibitors targeting non-small-cell lung cancer (NSCLC), focusing on their mechanisms, efficacy, and clinical trial statuses. Key small molecules such as RM-018 and RMC-4998 highlight novel approaches in targeting the KRASG12C mutation, offering enhanced potency compared to earlier inhibitors. Traditional and plant-derived compounds, including Fuzi alkaloids, salvianolic acid, and ononin, demonstrate promising antitumor activities through diverse pathways, such as the PI3K/AKT/mTOR signaling axis. Combination therapies targeting dual pathways show synergistic effects, improving treatment efficacy. The role of personalized medicine, driven by genetic profiling and pathway-specific inhibitors, is emphasized as a transformative approach in NSCLC management. These findings highlight the potential of mTOR-targeting agents as a cornerstone in advancing NSCLC therapies.1 Introduction2 Small-Molecule mTOR Inhibitors3 mTOR Inhibitors in Clinical Trials4 Conclusion and Future Directions
Keywords: mTOR; small molecules; rapalogs; clinical trials; cancer